2006
DOI: 10.1111/j.1538-7836.2006.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant and anti‐inflammatory effects after peritoneal lavage with antithrombin in experimental polymicrobial peritonitis

Abstract: Summary. Background: In sepsis, coagulation inhibition using high-dose systemic antithrombin (AT) tends to improve survival. However, systemic AT use is complicated by increased risk of bleeding (odds ratio 1,7) and clinically important survival increase is seen only in the non-heparinized subgroup. Local (intra-abdominal) inhibition of coagulation with AT may be more effective. Objectives: To investigate effects of intraabdominal high-dose recombinant human AT (rhAT) lavage on coagulation and inflammation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In our study, haemostatic disturbances associated with endotoxin-induced DIC were not suppressed as required by treatment with VIP. Some experimental studies have reported that AT is a good predictor of mortality in sepsis patients (9,27). In the present study, the observed decrease in plasma AT activity in LPS group is consistent with the results of previous in vitro and in vivo investigations (4,30).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, haemostatic disturbances associated with endotoxin-induced DIC were not suppressed as required by treatment with VIP. Some experimental studies have reported that AT is a good predictor of mortality in sepsis patients (9,27). In the present study, the observed decrease in plasma AT activity in LPS group is consistent with the results of previous in vitro and in vivo investigations (4,30).…”
Section: Discussionsupporting
confidence: 93%
“…diseases. [11][12][13][14] Collectively, the expression and activity changes of coagulation system components following infection favor the rapid generation of fibrin matrices. An uncontrolled coagulation response following infection can lead to disseminated intravascular coagulation (DIC), a consumptive coagulopathy.…”
mentioning
confidence: 99%
“…It was recently demonstrated that the TF/FVIIa pathway was involved in a mouse model of abdominal sepsis induced by Escherichia coli (9) and that the inhibition of this pathway by recombinant nematode anticoagulant protein c2 (rNAPc2) did reduce thrombin generation and fibrin deposition without affecting the inflammatory or antibacterial response. In experimental polymicrobial peritonitis, it was demonstrated that a peritoneal lavage with recombinant human antithrombin (rhAT) inhibited coagulation and reduced neutrophil recruitment and local cytokine concentrations, ultimately improving survival (10). The inhibition of TF may therefore be useful to avoid fibrin deposition in organs without compromising the host defence.…”
Section: Resultsmentioning
confidence: 99%